Round‐robin test for the measurement of layer thickness of multilayer films by secondary ion mass spectrometry depth profiling. (27th July 2017) - Kim, Kyung Joong; Jang, Jong Shik; Bennett, Joe; Simons, David; Barozzi, Mario; Takano, Akio; Li, Zhanping; Magee, Charles
Abstract : An international round‐robin test (RRT) was performed to investigate a method to determine the interface location and the layer thickness of multilayer films by secondary ion mass spectrometry (SIMS) depth profiling as a preliminary study to develop a new work item proposal in ISO/TC‐201. Two types of reference materials were used in this RRT. A SiGe alloy (Si52.4 Ge47.6 ) reference film was used to determine the relative sensitivity factors of Si and Ge. A Si/Ge multilayer reference film was used to determine the relative sputtering rates of the Si and Ge layers. The layer thicknesses were measured from the interfaces determined by a 50 atomic percent definition. Seven laboratories from 5 countries participated in this international RRT. The RRT reference expanded uncertainties for Si and Ge layers in a Si/Ge multilayer with similar thicknesses as the reference film were 0.76 and 1.17 nm, respectively. However, those in a thinner Si/Ge multilayer film were slightly larger at 1.04 and 1.59 nm, respectively. Most of the thickness ratios in the 2 Si/Ge multilayer films were consistent with the RRT reference value within their expanded uncertainties.